2016
DOI: 10.1002/pat.3960
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the 3D‐printed plastic parts and predicting the mechanical properties using artificial neural networks

Abstract: This study investigates the mechanical properties of 3D‐printed plastic parts fabricated using Fused Deposition Modeling (FDM). For this purpose, a 3D printer named KASAME was designed and built by the researchers. The test samples were fabricated using polylactic acid (PLA). The experiments were conducted using three melt temperatures (190°C, 205°C, and 220°C), four layer thickness values (0.06 mm, 0.10 mm, 0.19 mm, and 0.35 mm), and three raster pattern orientations (+45°/−45° [the crisscross pattern], horiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 31 publications
2
55
0
3
Order By: Relevance
“…It has to be pointed out that, in this research, only the polymer component (45% vol.) was melted during the FFF process; therefore, the effect of extrusion temperature on tensile properties was not as strong as in case of FFF of pure polymer material [46][47][48][49][50][51][52][53].…”
Section: Statistical Analysis Of Tensile Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…It has to be pointed out that, in this research, only the polymer component (45% vol.) was melted during the FFF process; therefore, the effect of extrusion temperature on tensile properties was not as strong as in case of FFF of pure polymer material [46][47][48][49][50][51][52][53].…”
Section: Statistical Analysis Of Tensile Strengthmentioning
confidence: 99%
“…Several studies are available where the tensile properties of polymeric parts produced by MEAM were investigated. For example, Bayraktar et al [46], Alafaghani et al [47], Chacon et al [48], and Spoerk et al [49] investigated PLA (Polylactic Acid) parts; Ahn et al [50], Reddy et al [51], and Álvarez et al [52] investigated ABS parts; finally, Spoerk et al [53] investigated filled polypropylene. However, information of the optimization of the printing conditions to improve the tensile properties of feedstocks to obtain high-quality sintered metallic parts shaped by FFF is not available in the open literature.…”
Section: Introductionmentioning
confidence: 99%
“…The technology generally is not considered suitable for more intricate designs or where high strength is required [8]. Usually, the parts manufactured with this technique can exhibit some internal anisotropy due to layering procedure [9].…”
Section: Fused Deposition Modeling (Fdm)mentioning
confidence: 99%
“…Advances in technology have led to new developments in the manufacturing of products in industry . One such development is the manufacturing of products using additive manufacturing technologies, which are now being increasingly used across many industries to create functional products at low cost with superior mechanical properties such tensile strength, impact strength, flexural modulus, compression strength and wear, and friction resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The results have also shown that the presence of micro‐hills and micro‐pulling are the main reasons for the improved tensile strength with raster angle of 0 ° . Bayraktar et al investigated the mechanical properties of polylactic acid parts manufactured by FDM through studying and optimizing various processing parameters. This study concluded that raster angle is the most influential factor.…”
Section: Introductionmentioning
confidence: 99%